Development of application-based badminton material teaching media for middle school level PJOK teachers - Ari Wibowo Kurniawan; Lokananta Teguh Hari Wiguno; M. Helmy Firman Amrullah (Journal of Science and Education (JSE), 2022)
This development research has the goal of developing application-based badminton game learning using the Java programming language which is used as a supporting tool for learning badminton game material for Middle School PJOK Teachers in Kediri Regency as well as being a reference and development for further research. This research method refers to the development research method of Sugiono, which. The test subjects in this study involved 40 SMP PJOK teachers in Kediri Regency, consisting of 10 teachers involved in the small group trial and 30 teachers involved in the large group trial. The results of the analysis carried out by experts who have carried out the validity of this application product, the percentage of learning expert evaluations is obtained, which means it is very valid, the results of the evaluation of badminton playing experts mean it is very valid, the results of the evaluation of media experts mean it is very valid. So based on these results, the research product of this badminton material learning application application was declared "fit for use" for learning badminton game material for junior high school PJOK teachers in Kediri Regency.